2020
DOI: 10.1186/s12951-020-0579-7
|View full text |Cite
|
Sign up to set email alerts
|

Ternary nanocomposite carriers based on organic clay-lipid vesicles as an effective colon-targeted drug delivery system: preparation and in vitro/in vivo characterization

Abstract: This study aimed to develop a new colon-targeted drug delivery system via the preparation of ternary nanocomposite carriers based on organic polymer, aminoclay and lipid vesicles. Budesonide (Bud), an anti-inflammatory drug was chosen as a model drug and encapsulated into three different formulations: liposome (Bud-Lip), aminoclay-coated liposome (AC-Bud-Lip), and Eudragit ® S100-aminoclay double coated liposome (EAC-Bud-Lip). The formation of the aminoclay-lipid vesicle nanocomposite was confirmed by energy d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 40 publications
(45 reference statements)
3
19
0
Order By: Relevance
“…This indicates that the absorption mechanism of the liposomes is related to the phagocytic property of macrophages [46]. Furthermore, a previous study of nanocomposite carriers using aminoclay and Eudragit in LPS-stimulated RAW 264.7 cells, found no toxicity to macrophages [45]. The results of these publications, taken together with those of the current study, indicate that these nanocomposites may be good candidates as carriers for oral drug delivery.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This indicates that the absorption mechanism of the liposomes is related to the phagocytic property of macrophages [46]. Furthermore, a previous study of nanocomposite carriers using aminoclay and Eudragit in LPS-stimulated RAW 264.7 cells, found no toxicity to macrophages [45]. The results of these publications, taken together with those of the current study, indicate that these nanocomposites may be good candidates as carriers for oral drug delivery.…”
Section: Discussionsupporting
confidence: 78%
“…In this study, we orally administered IFX targeting the colon using liposomes, aminoclay, and Eudragit S100-based nanocomposite carriers. In previous studies, in vivo image analysis by confocal microscopy confirmed the effective intracellular distribution of fluorescently labeled nanocomposite carriers in the colon [44,45]. The expression of each macrophage marker gene and the accumulation of liposomes showed a significant positive correlation, and liposomes enhanced the accumulation of drug candidates through macrophages in damaged colon tissues [46].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In this study, we orally administered IFX targeting the colon using liposomes, aminoclay, and Eudragit S100-based nanocomposite carriers. In previous studies, in vivo image analysis by confocal microscopy con rmed the effective intracellular distribution of uorescently labeled nanocomposite carriers in the colon [44,45]. The expression of each macrophage marker gene and the accumulation of liposomes showed a signi cant positive correlation, and liposomes enhanced the accumulation of drug candidates through macrophages in damaged colon tissues [46].…”
Section: Discussionmentioning
confidence: 84%
“…In this study, we orally administered IFX targeting the colon using liposomes, aminoclay, and Eudragit S100-based nanocomposite carriers. In previous studies, in vivo image analysis by confocal microscopy con rmed the effective intracellular distribution of uorescently labeled nanocomposite carriers in the colon [38,39]. The expression of each macrophage marker gene and the accumulation of liposomes showed a signi cant positive correlation, and liposomes enhanced the accumulation of drug candidates through macrophages in damaged colon tissues [40].…”
Section: Discussionmentioning
confidence: 84%